Pendekatan Pendidikan Islam dan Ekonomi Syariah Terhadap Fenomena Inner Child dan Self-Reward - Hamzah Muchtar, Evan (STAI Asy-Syukriyyah, 2025)
The phenomena of inner child and self-reward have increasingly become part of popular culture, particularly among millennials and Gen Z, driven by social media narratives that emphasize emotional healing and self-appreciation. This article aims to examine these phenomena through the lens of Islamic education and sharia economics. Using a qualitative phenomenological approach, data were collected through non-participant observation of digital content portraying healing-oriented self-reward practices. The findings reveal that self-reward can serve as a medium for emotional healing and educational development when aligned with Islamic values such as tazkiyah al-nafs (purification of the soul), maslahah (public benefit), and spiritual discipline. Therefore, an integrated approach based on Islamic education and sharia economics is essential to guide these practices beyond mere consumerism—transforming them into a meaningful process of character building, soul purification, and the pursuit of a balanced life blessed by Allah.